A new species of the bark louse genus Clematoscenea (Psocodea: Psocidae) from Xizang, China - Jie, Lulan; Liu, Xingyue (Zootaxa, 2021)
A new species of the bark louse genus Clematoscenea Enderlein, 1907, namely Clematoscenea biprocessus sp. n., is described from Xizang Autonomous Region, China. The new species can be diagnosed by the forewing with a nearly V-shaped brown marking on proximal half in female but hyaline on corresponding region in male, and by the abdomen dorsally with a yellow band. Keys to species of Clematoscenea based on male and female characters are also provided.